Dimensions of Parental Alcohol Use/Problems and Offspring Temperament, Externalizing Behaviors, and Alcohol Use/Problems. (29th July 2013) - Kendler, Kenneth S.; Gardner, Charles O.; Edwards, Alexis; Hickman, Matt; Heron, Jon; Macleod, John; Lewis, Glyn; Dick, Danielle M.
<x xml:space="preserve">Abstract</x> Background Alcohol consumption (AC) and alcohol problems (AP) are complex traits. How many factors reflecting parental AC and AP are present in the large prospectively followed Avon Longitudinal Study of Parents and Children cohort? Would these factors be uniquely associated with various temperamental and alcohol‐related outcomes in the children? Methods We factor‐analyzed multiple items reflecting maternal and paternal AC and AP measured over a 12‐year period from before the birth of the child (n = 14, 093 families). We examined, by linear regression controlling for socioeconomic status, the relationship between scales derived from these factors and offspring early childhood temperament, externalizing traits, and adolescent AC and AP (ns ranging from 9, 732 to 3, 454). Results We identified 5 coherent factors: typical maternal AC, maternal AC during pregnancy, maternal AP, paternal AC, and paternal AP. In univariate analyses, maternal and paternal AC and AP were modestly and significantly associated with low shyness, sociability, hyperactivity, and conduct problems in childhood and early adolescence; delinquent behavior at age 15; and AC and AP at ages 15 and 18. AC and AP at age 18 were more strongly predicted by parental factors than at age 15. Maternal AC during pregnancy uniquely predicted externalizing traits at ages 4, 13, and 15. Conclusions Parental AC and AP are complex multidimensional traits that differ in their association with a range of relevant measures in their children. Controlling for background AC and AP, self‐reported levels of maternal AC during pregnancy uniquely predicted externalizing behaviors in childhood and adolescence.